An Extension of Two Results of Hardy - Rhoades, B. E. (Sarajevo Journal of Mathematics, 2024)
In this paper we extend two results of Hardy, dealing with regular weighted mean matrices, to coregular factorable matrices. 2010 Mathematics Subject Classification. Primary: 40G99; Secondary: 40C05.